Conception rate hasil inseminasi buatan menggunakan semen sexing beku pada Sapi Persilangan Ongole - Yekti, Aulia Puspita Anugra; Kurniaesa, Titah Ulya; Isnaini, Nurul; Kuswati, Kuswati; Susilawati, Trinil (Faculty of Animal Science, Universitas Brawijaya, 2018)
Artificial Insemination (AI) is a technique that is widely used by farmers to improve the genetic quality of livestock. This method can be increased in value by using sexing semen that can regulate and produce the sex of the offspring as expected. The purpose of this study was to determine the success of AI by using frozen sexing semen on Ongole Crossbred cows in Malang Regency. The materials used were 98 Ongole crossbred cows in traditional farm of Malang Regency especially in Pakis, Tumpang, Jabung and Singosari Districts. The method used was a field experiment with two treatments: 49 cows were inseminated by using frozen sexing semen (P1) and 49 cows were inseminated by using non sexing semen (P0). The variables observed were the Non-Return Rate (NRR) value observedin 3 estrous cycle after AI and CR value based on pregnancy observation at 8 months of pregnancy. Data were analyzed descriptively and continued with a one-proportion z-test. The datashowed that the CR value on P1; P0 were 55.10% and 65, 31% respectively.furthemore, the NRR value on P1 from NRR1 to NRR3 were 87,76%, 73,47% and 67,35%, while on P0 95,92%, 83,67% and 75,51% respectively.It can be conclude thatCR and NRR value of sexing semenwas lower than non sexing semen, however sexing semen can be applied for certain purposes such as producing offspring as expected